HIP to be Square: Simplifying Nitridophosphate Synthesis in a Hot Isostatic Press. (18th August 2020) - Wendl, Sebastian; Mardazad, Sara; Strobel, Philipp; Schmidt, Peter J.; Schnick, Wolfgang
Abstract: (Oxo)Nitridophosphates have recently been identified as a promising compound class for application in the field of solid‐state lighting. Especially, the latest medium‐pressure syntheses under ammonothermal conditions draw attention of the semiconductor and lighting industry on nitridophosphates. In this contribution, we introduce hot isostatic presses as a new type of medium‐pressure synthetic tool, further simplifying nitridophosphate synthesis. In a second step, phosphorus nitride was replaced as starting material by red phosphorus, enabling the synthesis of Ca2 PN3 as model compound, starting only from readily available compounds. Moreover, first luminescence investigations on Eu 2+ ‐doped samples reveal Ca2 PN3 :Eu 2+ as a promising broad‐band red‐emitter ( λ em =650 nm; fwhm=1972 cm −1 ). Besides simple handling, the presented synthetic method offers access to large sample volumes, and the underlying reaction conditions facilitate single‐crystal growth, required for excellent optical properties. Abstract : Hot isostatic pressing is introduced as easy and fast synthetic access to nitridophosphate phosphors, while providing large‐scale quantities. In particular, the calcium nitridophosphate Ca2 PN3 :Eu 2+ was synthesized under medium‐pressure conditions (150 MPa N2, 1200 °C), revealing single crystals with remarkable size (>100 μm) and quality. Further, Ca2 PN3 :Eu 2+ shows a rather narrow deep‐red emission and notable high internal quantum efficiency.